PENANAMAN NILAI-NILAI KEDISIPLINAN DI SMP AL-RIFA’IE - Iftin Mufariha; Ika Ratih Sulistiani; Ika Anggraheni (VICRATINA, 2020)
Education is an important thing in life. It is the thing that is behind Al-Rifa'ie junior High School to always create an educational institution that is in the environment of Pesantren. Researchers formulate problems, about what efforts teachers are doing to instill discipline, and what factors impede teachers in the discipline of disciplinary action. The above research is done with qualitative type. Data collection procedures are conducted using observation methods that are observations, interview methods that are using the path of verbal questions with research sources. According to the observation done then it can be known that with the establishment of a OSIS that works with Waka Kesiswaan SMP Al-Rifa'ie, the application of discipline at this time was realized as much as 60%. Factors that support the planting of discipline come from all parties, institutions, teachers, students and environment.